A Phytophthora capsici effector suppresses plant immunity via interaction with EDS1 - Li, Qi (Mol Plant Pathol, 2020)
EDS1 (Enhanced Disease Susceptibility 1) plays a crucial role in both effector‐triggered immunity activation and plant basal defence. However, whether pathogen effectors can target EDS1 or an EDS1‐related pathway to manipulate immunity is rarely reported. In this study, we identified a Phytophthora capsici Avirulence Homolog (Avh) RxLR (Arg‐any amino acid‐Leu‐Arg) effector PcAvh103 that interacts with EDS1. We demonstrated that PcAvh103 can facilitate P. capsici infection and is required for pathogen virulence. Furthermore, genetic evidence showed that PcAvh103 contributes to virulence through targeting EDS1. Finally, PcAvh103 specifically interacts with the lipase domain of EDS1 and can promote the disassociation of EDS1–PAD4 (Phytoalexin Deficient 4) complex in planta. Together, our results revealed that the P. capsici RxLR effector PcAvh103 targets host EDS1 to suppress plant immunity, probably through disrupting the EDS1–PAD4 immune signalling pathway.